2007
DOI: 10.1007/s00213-007-0906-9
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral hippocampal volume increases after long-term lithium treatment in patients with bipolar disorder: a longitudinal MRI study

Abstract: Consistent with preclinical literature supporting the neuroprotective effects of lithium, long-term treatment is associated with preservation of recollective memory function and increased hippocampal size in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
121
1
9

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(143 citation statements)
references
References 89 publications
10
121
1
9
Order By: Relevance
“…[14][15][16][17][18] However, most of these studies were confounded by effects of medication, which is known to increase mesiotemporal volumes. 21 We controlled for potential confounding effect of medication in the design of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18] However, most of these studies were confounded by effects of medication, which is known to increase mesiotemporal volumes. 21 We controlled for potential confounding effect of medication in the design of our study.…”
Section: Discussionmentioning
confidence: 99%
“…If mesiotemporal volumes are an endophenotype for BD, then affected offspring should show the largest differences relative to control subjects, with intermediate volumes among unaffected patients. As most studies reported lack of hippocampal volume changes 21 and decreased amygdala volumes in young patients with BD, 20 we expected to find comparable hippocampal and decreased amygdala volumes both in affected and in unaffected offspring of patients with BD relative to control subjects.…”
mentioning
confidence: 86%
“…Lithium treatment has been associated with increased gray matter volumes in general [Moore et al 2000], and in particular brain regions such as the hippocampus [Foland et al 2008;Yucel et al 2007], and the amygdala [Usher et al 2010;Foland et al 2008]. Recently, several studies have examined whether such gray matter changes correlate with lithium response rather than simply treatment.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…1,2 Some neuroimaging studies have reported findings suggestive of similar effects of Li in humans, [3][4][5][6][7] although the data continue to be limited and inconsistent. [8][9][10][11][12][13] Smaller hippocampal volumes are among the most replicated neuroimaging findings in patients with major depressive disorder compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium treatment leads to increased hippocampal volumes reported in pro spective studies. 7 Lithiumexposed patients in retrospective studies have typically shown larger hippocampal volumes than unmedicated participants. 26,47,48 Thus, it is possible that hippocampal volume changes in patients with bipolar disorder are masked by exposure to putative neuroprotective effects of Li.…”
Section: Introductionmentioning
confidence: 99%